2022
DOI: 10.1002/jcph.2088
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Effects of Metformin in Men With Early‐Onset Androgenic Alopecia

Abstract: Males with early-onset androgenic alopecia are characterized by elevated androgen levels. The aim of the present study was to investigate whether the presence of this condition modulates the impact of metformin on pituitary hormone production. This study compared 2 groups of young men with prediabetes, matched for age, blood pressure, and insulin sensitivity: 23 subjects with early-onset male-pattern baldness (group 1) and 25 individuals with normal hair growth (group 2). Throughout the study, both groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This observation is in line with the results of previous studies including male subjects. In individuals with early-onset male-pattern hair loss, considered the equivalent of PCOS in men [28], metformin produced a neutral effect on plasma prolactin [29], while in hypogonadal men with prolactin excess, the decrease in plasma prolactin was observed only in patients not receiving exogenous testosterone [22]. The current study is the first to show similar relationships between hyperandrogenism and the absence of prolactinlowering properties in women.…”
Section: Discussionsupporting
confidence: 57%
“…This observation is in line with the results of previous studies including male subjects. In individuals with early-onset male-pattern hair loss, considered the equivalent of PCOS in men [28], metformin produced a neutral effect on plasma prolactin [29], while in hypogonadal men with prolactin excess, the decrease in plasma prolactin was observed only in patients not receiving exogenous testosterone [22]. The current study is the first to show similar relationships between hyperandrogenism and the absence of prolactinlowering properties in women.…”
Section: Discussionsupporting
confidence: 57%
“…These were all case-control studies. The results showed that men with early-onset AGA may experience less benefit from rosuvastatin [ 64 ], metformin [ 65 , 66 ], lisinopril [ 67 ], levothyroxine [ 68 ], Vitamin D [ 69 ], or bromocriptine [ 70 ] when treating dyslipidemia, prediabetes, hypertension, autoimmune hypothyroidism, autoimmune thyroiditis, or prolactin excess, respectively, compared to the contemporaries without alopecia. However, one exception was noted, as the impact of metformin on gonadotroph secretory function appeared to be stronger in men with early-onset AGA compared to those with normal hair growth [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this emphasizes the importance of lifestyle modifications in individuals with early-onset AGA to prevent these co-existing health conditions. Furthermore, men with early-onset AGA may benefit to a lesser degree from treatments such as rosuvastatin [ 64 ], metformin [ 65 , 66 ], or lisinopril [ 67 ] compared to individuals with normal hair growth. Therefore, young patients with AGA may not only be more susceptible to developing metabolic diseases, but also less responsive to certain treatments.…”
Section: Discussionmentioning
confidence: 99%